Profiling morpho-syntactical development of cochlear implanted children with TR-LARSP - Yaşar, Özlem Cangökçe; Topbaş, Seyhun (Taylor and Francis Ltd., 2018)
This research aims to describe the grammatical development of Turkish-speaking children with cochlear implants (CI) using the Turkish adaptation of the Language Assessment and Remediation Profile (LARSP). The study was conducted on a total of 15 children with CIs aged 43-87months with 22-45months of hearing age. A total of 750 utterances were elicited from the CI group's recorded speech samples and analysed using the methodology of Turkish-Language Assessment and Remediation Profile (TR-LARSP). A cross-sectional descriptive model is used in the study. The results show that there is a significant difference in the acquisition of grammatical structures in children with CIs as compared to typically developing (TD) age-matched children in Turkish. In conclusion, this study suggests that after the implantation of these children, the speech therapist should consider the acquisition time of morpho-syntactical structures before making a language-based therapy plan.
WOS: 000424343400001
PubMed ID: 28786695
Keywords: Cochlear Implant; Hearing Impairment; Language; Morpho-Syntactical Development; TR-LARSP